Evaluation globale de la résistance des bananiers à la fusariose, aux maladies foliaires causées par les Mycosphaerella spp. et aux nématodes : evaluation de la performance - Carlier, J.; Waele, D. de; Escalant, J-V.; Vézina, A.; Picq, C.; International Network for the Improvement of Banana and Plantain (2002)
This technical guidelines replace the Technical Guidelines 1 (Screening of Musa germplasm for resistance and tolerance to nematodes) and 3 (Evaluation of Musa germplasm for resistance to Sigatoka diseases and Fusarium wilt) as far as performance evaluations are concerned. Technical Guidelines for in-depth evaluations, which were also part of Technical Guidelines 3, are published separately. The Fusarium wilt and Mycosphaerella leaf spot sections have been updated following recommendations and comments made after analysing IMTP II results.